Analysis of Factors Affecting the Export of Batik in Indonesia - Dwi Joko Siswanto; Erlyn Shukma Dewi; Ickhsanto Wahyudi; Tantri Yanuar Rahmat Syah (Journal of Social Science, 2022)
This study aims to determine whether the exchange rate, GDP, and inflation affect Batik exports in Indonesia. The data used in this study are secondary time series data from 2010-2020. The data used were obtained from the Ministry of Industry, the Central Bureau of Statistics, and Bank Indonesia. This type of research is associative research using quantitative methods. The test is carried out using the help of statistical software Eviews 10. The analysis method used is descriptive statistics, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that the Exchange Rate variable has a positive but insignificant effect on Indonesian Batik Exports. The GDP variable has a negative and significant effect on Indonesian Batik Exports. The Inflation variable has a positive and significant effect on Indonesian Batik Exports for the period 2010-2020. Exchange Rate, GDP, and Inflation simultaneously have a significant effect on Indonesian Batik Exports. The coefficient of determination is 0.551197, which means that the independent variables exchange rate, GDP, and inflation affect 55.11% of the dependent variable Batik exports in Indonesia.